Pertimbangan Hukum Hakim Dalam Penjatuhan Pidana Perkara Pencurian Pemberatan (Vide Pasal 363 Ayat 1 Kuhpidana) - Malaihollo, Aditya Putra Mentari; Pasalbessy, John Dirk; Sopacua, Margie Gladies (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: There are several types of theft crimes ranging from ordinary theft crimes (Article 362 of the Criminal Code), light theft crimes (Article 364 of the Criminal Code), crimes of aggravated or qualified theft (Article 363 of the Criminal Code), crimes of violent theft (Article 365 of the Criminal Code), crimes of theft in within the family (Article 367 of the Criminal Code) with a maximum sentence of 7 years in prison.Purposes of the Research:Analyzing and reviewing the application of Article 363 Paragraph (1) of the Criminal Code in resolving cases of theft and Analyzing Article 363 Paragraph (1) of the Criminal Code can be used as a basis for consideration in cases of theft with violence, as one of the requirements in completing studies at the Faculty of Law.Results of the Research:In the application of article 363 in the case of theft, the elements of article 363 can be applied, namely: Whoever, Takes something, With the intention of being owned, is against the law and is carried out at night in a house or a closed yard with a house. When all the elements in article 363 are met, the perpetrator's actions are determined as theft with weights but in the decision N0 18/Pid.B/20202/PN Msh this is not the case because the judge's decision is still too light even though the defendant's actions meet the weighting elements. Article 363 can be used as a basis for judges' considerations because the elements in Article 363 can be used by judges as a basis for consideration before the judge decides on a theft case, but in decision N0 18/Pid.B/20202/PN, the judge does not see the elements that have been fulfilled. by the defendant's actions so that the judge handed down a decision that was not in accordance with the provisions of Article 363 of the Criminal Code.